Network Planning Analysis Using The Critical Path Method (CPM) as an Evaluation Tool for Project Planning and Control (Case Study of a Residential House Development Project in Pare City, Kediri Regency) (Fakultas Ekonomi dan Bisnis, Universitas 17 Agustus 1945 Surabaya, 2023)
The construction of residential houses in Pare City Kediri Regency experienced problems in the construction process was late from the predetermined schedule, which resulted in increased costs incurred. This project is located in Pare City, Kediri Regency, on a land area of 1200 M² with a size of 120 x 10 M first construction is a 20 x 8 M residential house. According to the agreed plan and a master schedule, this project is expected to be completed within 80 working days, and every day only work for 8 hours reality the implementation of this project, various factors affect the progress of the work. The percentage of actual cumulative progress until the 4th week of January is 97.42% of the 100% master schedule plan, there is a deviation of 2. 58 & it can be seen that the achievement of progress from the previous month indicates a continuous delay from the monthly plans made. One of the methods that must be used to design Network Planning is the Critical Path Method (CPM). The CPM method is used to plan, schedule, and control project activities that are deterministic or single time after evaluation data is obtained so that time and cost are more efficient and effective in calculating evaluation data using the CPM method. The project, which was initially completed in 103 days at Rp. 213,956,500 after being evaluated, and if there were no mistakes during project implementation, the normal time was 72 days at Rp. 160,276. 500 and then using the CPM method obtained an effective time of 52 days and an efficiency cost of Rp. 115,755,240. Keywords: Critical path method (CPM), Network Planning, Acceleration, Time, Cost.